2023
DOI: 10.3390/life13112226
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Acute Coronary Syndrome

Panagiota K. Stampouloglou,
Artemis Anastasiou,
Evanthia Bletsa
et al.

Abstract: The global prevalence of diabetes mellitus (DM) has led to a pandemic, with significant microvascular and macrovascular complications including coronary artery disease (CAD), which worsen clinical outcomes and cardiovascular prognosis. Patients with both acute coronary syndrome (ACS) and DM have worse prognosis and several pathophysiologic mechanisms have been implicated including, insulin resistance, hyperglycemia, endothelial dysfunction, platelet activation and aggregations as well as plaque characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 139 publications
(155 reference statements)
0
1
0
2
Order By: Relevance
“…Moreover, they showed that type II diabetes (itself an inflammatory condition) is an independent predictor of elevated calprotectin levels [ 77 ]. Similarly, diabetes has been shown to have associations with worse prognosis in ACS [ 78 , 79 ]. Moreover, Peng et al showed that regardless of the clinical manifestation of CAD, serum calprotectin levels were positively correlated with the severity of CAD in diabetic patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that type II diabetes (itself an inflammatory condition) is an independent predictor of elevated calprotectin levels [ 77 ]. Similarly, diabetes has been shown to have associations with worse prognosis in ACS [ 78 , 79 ]. Moreover, Peng et al showed that regardless of the clinical manifestation of CAD, serum calprotectin levels were positively correlated with the severity of CAD in diabetic patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generation mit Zotarolimusoder Everolimus-Beschichtung ist dagegen eine akzeptable therapeutische Alternative bei Patienten mit weniger stark ausgeprägtem Koronarbefund. Studien und retrospektive Analysen konnten beim Vergleich von PCI zur ACB-Operation bei Mehrgefäß-KHK keinen statistisch signifikanten Vorteil weder für die PCI mit 2nd-Generation-DES (DES: Drug-eluting Stents) noch für die ACB-Operation in Bezug auf die Mortalität nachweisen [3,7]. Die Entscheidung über die optimale Revaskularisationstherapie bei T2DM und Mehrgefäß-KHK sollte auch unter Zuhilfenahme des SYNTAX-Scores erfolgen.…”
Section: Koronare Mehrgefäßerkrankung Und Diabetesunclassified
“…Die komplexere Koronarläsionsmorphologie mit Beteiligung mehrerer Gefäße und die häufige Mitbeteiligung des linkskoronaren Hauptstamms macht bei Patienten mit T2DM die Entscheidung und Auswahl der optimalen Revaskularisationsstrategie gerade bei symptomatischen Patienten mit ACS noch herausfordernder. Aktuelle Daten legen nahe, dass die Langzeitprognose bei diabetischen Patienten mit Mehrgefäßerkrankung und ACS durch eine ACB-Operation verbessert werden kann [3]. Bei Patienten mit Diabetes und NSTE-ACS sollten sich das Timing und die Indikation zur Koronarintervention nicht von dem Vorgehen bei nicht diabetischen Patienten unterscheiden [7,17].…”
Section: Akutes Koronarsyndrom Und Diabetes Mellitusunclassified